156k views
5 votes
Sydney applied the steps below to find the product of (3.1)(–1.6). Step 1: (3.1)(–1.6) = (–1.6)(3.1) Step 2: = _______________ Step 3: = (–4.8) + (–0.16) Step 4: = –4.96 Which expression correctly fills in the blank in Step 2?

User Raek
by
4.4k points

2 Answers

7 votes

Answer:

it might be D

Explanation:

sorry is im wrong

EDIT

on edge im right!!!!!!!!!!!!!!

User Yikouniao
by
4.6k points
3 votes

Answer:

(-1.6)(3 + 0.1)

Explanation:

Sidney applied the steps to find the product of two numbers (3.1) and (-1.6),

Step 1,

(3.1)(-1.6) = (-1.6)(3.1)

Step 2,

(-1.6)(3.1) = (-1.6)(3 + 0.1)

Step 3,

(-1.6)(3 + 0.1) = -4.8 + (-0.16) [Distributive property]

Step 4,

-4.8 + (-0.16) = -4.96

Therefore, expression that correctly fits in step 2 will be,

(-1.6)(3 + 0.1)

User Grr
by
4.8k points